NÍVEIS DE SUPORTE DO TRANSTORNO DO ESPECTRO AUTISTA E MOBILIDADE FUNCIONAL: ESTUDO TRANSVERSAL (CIPEEX, 2026)
Introduction: Motor aspects have become an important focus of current studies on Autism Spectrum Disorder (ASD), mainly due to alterations in gait and functional mobility. Objective: To evaluate the functional mobility of children with ASD according to the DSM-5 levels of support. Methods: Cross-sectional study with 25 children aged three to eight years, categorized by support level as Level 1 (n=8), Level 2 (n=6), and Level 3 (n=11). Disorder severity was assessed using the Childhood Autism Rating Scale (CARS). Functional mobility was assessed with the Timed Up and Go (TUG) test using an inertial sensor. Data were analyzed statistically.Results: Statistical analysis showed no difference in TUG execution time among the three support levels (p=0.46).Conclusion: In this sample of children with ASD, support levels did not influence functional mobility.